ANALISIS SEMIOTIKA TENTANG MAKNA PERAN ISTRI DALAM FILM SURGA YANG TAK DIRINDUKAN 3 - Kristanty, Shinta; G. Pratikto, Riyodina; Romadhon, Muhammad Syahru (Universitas Budi Luhur, 2023)
This study intends to explain and describe how the meaning of the role of the wife is contained in the filmSurga yang Tak Dirindukan 3. This study aims to determine the meaning of the wife's role in the film Surga yang Tak Dirindukan 3. This study uses the concept of film and Charles Sanders Peirce's theory of semiotics. The research method used is Charles Sanders Peirce's Semiotics, with a qualitative research approach. The paradigm of this research refers to the Constructivism paradigm. The result of this research is that there is a meaning that the wife is not only a life partner but can be a friend when sad, when the husband falls, the wife can be a giver of encouragement and support, as well as controlling the situation when the husband carries out activities. The conclusion of this research is that the researcher found 3 scenes that represent the meaning of the wife's role in the film Surga yang Tak Dirindukan 3, including: the wife as a life partner, as a life companion who is wise in giving advice to her husband, as a support for the husband. the meaning of the role of the wife can be emulated by the wife in general. Keywords: Film, Semiotics, Role, Wife